CRITICAL REVIEW: IS RELIGIOUSITY AN IMPORTANT DETERMINANT ON MUSLIM CONSUMER BEHAVIOR IN MALAYSIA - Fasa, Muhammad Iqbal (IJRDO - Journal of Applied Management Science, 2016)
In a constantly changing and increasingly globalized world, the construct of culture and subculture have become increasingly central to the consumer behavior literature. Religion still plays a significant role in influencing social and consumer behavior. Religious belief is a significant factor in influencing consumption behavior because by the rules and taboos it inspires. Furthermore, religiosity represents an inherent human value which tends stable over a fairly long period of time, and finally, many elements of religiosity are observable, and therefore of pragmatic value to marketers (Khraim, 2010). Islam is a religion that guides Muslims in every aspect of life, not just in specific acts of worship. For instance, in the Quranic verse, Al Isra’:26-27, Allah commands Muslims not to consume or spend extravagantly, but to spend in a way of Allah. Some other guidance which have been provided for by Islam are how and what to trade, how to interact with others and what can be consumed. Eating and drinking are strictly followed according to the Islamic rules in the everyday life of the Muslim society. But these norms however vary between different religious faiths and degree of observation. This discussion note provides comments on the issue, in particular the one under the notion of muslim consumer behavior in Malaysia written by Bro Syed Shah Alam, Bro Rohani Mohd, and Bro. Badrul Hisham.